Australia‐wide point prevalence survey of the use and appropriateness of antimicrobial prescribing for children in hospital. Issue 11 (24th November 2014) - Osowicki, Joshua; Gwee, Amanda; Noronha, Jesuina; Palasanthiran, Pamela; McMullan, Brendan; Britton, Philip N; Isaacs, David; Lai, Tony; Nourse, Clare; Avent, Minyon; Moriarty, Paul; Clark, Julia; et al.
Abstract: Objectives: To describe antimicrobial use in hospitalised Australian children and to analyse the appropriateness of this antimicrobial use. Design: Multicentre single‐day hospital‐wide point prevalence survey, conducted in conjunction with the Antimicrobial Resistance and Prescribing in European Children study. Setting: Eight children's hospitals across five Australian states, surveyed during late spring and early summer 2012. Patients: Children and adolescents who were inpatients at 8 am on the day of the survey. Main outcome measures: Quantity and quality of antimicrobial prescribing. Results: Of 1373 patients, 631 (46%) were prescribed at least one antimicrobial agent, 198 (31%) of whom were < 1 year old. The highest antimicrobial prescribing rates were in haematology and oncology wards (76% [95/125]) and paediatric intensive care units (55% [44/80]). Of 1174 antimicrobial prescriptions, 550 (47%) were for community‐acquired infections, 175 (15%) were for hospital‐acquired infections and 437 (37%) were for prophylaxis. Empirical treatment accounted for 72% of antimicrobial prescriptions for community‐acquired infections and 58% for hospital‐acquired infections (395 and 102 prescriptions, respectively). A total of 915 prescriptions (78%) were for antibacterials; antifungals and antivirals were predominantly used for prophylaxis. The most commonly prescribed antibacterials were narrow‐spectrum penicillins (18% [164 prescriptions]), β‐lactam–β‐lactamase inhibitor combinations (15% [136]) and aminoglycosides (14% [128]). Overall, 957 prescriptions (82%) were deemed appropriate, but this varied between hospitals (range, 66% [74/112]) to 95% [165/174]) and specialties (range, 65% [122/187] to 94% [204/217]). Among surgical patients, 65 of 187 antimicrobial prescriptions (35%) were deemed inappropriate, and a common reason for this was excessive prophylaxis duration. Conclusion: A point prevalence survey is a useful cross‐sectional method for quantifying antimicrobial use in paediatric populations. The value is significantly augmented by adding assessment of prescribing quality.